Effects of β-alanine supplementation on kickboxing-specific anaerobic performance, neuromuscular power, and strength endurance: A randomized, double-blind, placebo-controlled trial - Furkan Hasan Küçük; Cebrail Gençoğlu; Osman Ateş; Jonatas Deivyson Reis Da Silva Duarte; Dino Belošević; Salih Çabuk; Muhammet Raşit İnaç; Süleyman Ulupınar; Serhat Özbay (PLoS ONE, 2026)
β-Alanine (BA) elevates skeletal muscle carnosine and may improve repeated high-intensity performance; however, evidence in kickboxing is limited. This study investigated the effects of 4-week BA supplementation on sport-specific kickboxing anaerobic performance, neuromuscular power, and strength endurance in trained male kickboxers. Twenty-eight athletes were randomly assigned to BA (6.4 g·day ⁻ ¹; n = 14) or placebo (n = 14) in a double-blind, placebo-controlled design. Pre- and post-intervention assessments included the Kickboxing Anaerobic Speed Test (KAST₁–₅, KAST best , KAST total , Performance Decrement Index [PDI]), neuromuscular power (countermovement jump [CMJ], squat jump [SJ]), and strength endurance tests (push-up, pull-up). Baseline differences were tested via t -tests, effect sizes calculated according to Hedges’ g formula. Group × time effects were analyzed using two-way repeated-measures ANOVA with partial eta squared (ηp²) effect sizes. Baseline measures were comparable (all p > 0.05). After supplementation, no significant group × time interactions emerged for CMJ ( p = 0.148), SJ ( p = 0.717), KAST₁–₅ (all p > 0.05), KAST best ( p = 0.071), or PDI ( p = 0.454). However significant improvements were observed in the BA group for KAST total ( F (1,26) = 14.49, p < 0.001, ηp² = 0.358), push-ups ( F (1,26) = 5.89, p = 0.023, ηp² = 0.185), and pull-ups ( F (1,26) = 9.79, p = 0.004, ηp² = 0.274). Four weeks of BA supplementation enhanced total anaerobic performance (KAST total ) and upper-body strength endurance (push-up, pull-up), while no significant changes were observed in neuromuscular jump performance (CMJ, SJ). BA appears to be a practical ergogenic aid for improving repeated-effort and strength-endurance capacity in kickboxing. Clinical trial registration ClinicalTrials.gov ( NCT07319052 ).